Self-esteem and self-compassion status of migraine patients in Turkey: a multi-center study by Turkish Headache Study Group - Karakurum-Goksel, Basak; Ocal, Ruhsen; Van, Mert; Coskun, Ozlem; Karaaslan, Cihad; Ucler, Serap; Gokcay, Figen; Celebisoy, Nese; Sirin, Hadiye; Kisabay-Ak, Aysin; Saritas, Aysegul Seyma; Cerrahoglu-Sirin, Tuba; et al. (Frontiers in Neurology, 2025)
IntroductionMigraine, characterized by recurrent attacks, often necessitates a holistic approach for effective management. Treatment strategies aimed at enhancing self-esteem and self-compassion have been shown to reduce pain intensity in patients with chronic pain. This study aimed to investigate self-esteem and self-compassion in individuals with migraine.Materials and methodsThis multicentre, cross-sectional, case–control study included migraine patients evaluated at headache-specialized outpatient clinics across 22 centers in different regions of Turkey. 901 migraine patients and 901 healthy, matched controls were included. Neurologists specializing in headache disorders administered the Rosenberg Self-Esteem Scale, Self-Compassion Scale, Beck Depression Inventory, and Beck Anxiety Inventory to all participants. Data were compiled at a central site and subjected to statistical analysis.ResultsMigraine patients exhibited significantly lower self-esteem scores compared to healthy controls (p = 0.001 for both). Additionally, Beck Depression Inventory and Beck Anxiety Inventory scores were significantly higher in migraine patients (p = 0.001 for both). Although the mean self-compassion scores of migraine patients and healthy controls were comparable, a significant decline in self-compassion was observed among patients with higher migraine attack frequency.DiscussionIn conclusion, our findings indicate that migraine patients exhibit significantly higher levels of anxiety and depression compared to healthy controls. Self-esteem scores were also found to be lower in the migraine group. Although self-compassion scores were similar between the two groups, a noteworthy decline in self-compassion was observed in patients with higher migraine attack frequency. These results suggest that increased migraine severity may negatively impact patients’ emotional resilience, highlighting the potential value of integrating psychological support into migraine management, particularly for those with frequent attacks.